Stability characteristic of subsonic binary axisymmetric coaxial jets - Jhonatan Andrés Aguirre Manco (2019)
The performance of combustion systems in gas turbines and rocket engines depend strongly on the proper injection and mixing between fuel and oxidizer. The injection of propellants in these systems is performed using shear coaxial injectors that define the physical initial conditions for the combustion process. The hydrodynamic instabilities formed by the coaxial shear injector allow the mixing between the propellants through vorticity created by the instability of the shear layers. This work had as main objective the understanding of the stability characteristics of axisymmetric coaxial jets composed of different gases, specifically hydrogen and oxygen. To analyze the stability characteristics of coaxial binary jets the Linear Stability Theory (LST) and High Order Simulation (HOS) approaches were used. The LST has shown that the cases where the hydrogen was used as species in the inner jet H2 − O2 the amplification rates of Mode II are larger than the homogeneous coaxial jet, contrarily to what happens in O2 − H2 configuration. This agreed with the previous studies in a binary mixing layer, in which when the heavier species is in the lower velocity stream the amplification rates are larger, and vice versa. However For Mode I, the binary mixing layer results can not be extrapolated for a coaxial binary jet, once the confinement effect, caused by the finite quantity of species that can be placed in the inner jet, plays an important role. Using a low Mach number formulation, the compressible effects were neglected with the intention to show in the Less and Lin equation (compressible Rayleigh equation) where is the role of the species in the stability properties, which was called inertial effects. This formulation together with the compressible formulation also allows understanding the compressible effects caused by the different speed of sound of the species. Using High Order Simulations (HOS) of the Euler equation as second way to analyses the stability characteristics of coaxial binary jets, the main results of the LST were simulated in order to view different effects neglected by this theory, as: nonlinearities as modes interact, the used of realistic velocity and species profiles not based on canonical equations for the base flow and the visualization of the growth of the instabilities.